ANALYSIS OF FIGURATIVE LANGUAGE IN THE NOVEL THE KITE RUNNER - Rini Amir; Samsudin Hi. Adam; Agus Supriyadi (Jurnal Bilingual, 2024)
The purpose of this research is to find out and analyze the types of figurative language and its meaning in the novel "The kite Runner." This research uses a qualitative approach with content analysis. The main data source is the text in the novel "The Kite Runner." The data analysis technique in this research consists of data reduction, data presentation, and drawing conclusions. The results of this research, the researcher found 64 sentences of figurative language from five types of figurative language put forward by Leech (1981), namely personification indicated in as many as 18 sentences, similes indicated in as many as 18 sentences, metaphors indicated in as many as 4 sentences, hyperbole indicated in as many as 14 sentences, and metonymy indicated in as many as 10 sentences.